O poder e o sagrado na idade das trevas : a configuração simbólica da realeza homérica - Gabrecht, Ana Penha (2006)
The centuries XIIth to VIIIth b.C. of the Greek history period has been known by the historiography as Dark Ages. It is Dark Ages because in the Greece, in that time, the writing disappeared and it happened a notable reduction of material production. In such case, any information that we have about this age is specially based on the narratives of the poetry transmitted orally through generation by generation by poets known as aiodos. Homer was an aedos if he really existed. Ascribe him two great works assorted like epopee: the Iliad and the Odissey. Although to ponder that Homer has been lived during the VIIIth b.C., the poems have elements that report the century XIIth b.C. or before. The Homeric epics are important primary source to study power relations in the Dark Ages. The Iliad, as the main source for this research, gives us examples of the relation between the power and the sacred. Through this poem, it is possible realize that in Homeric world the power of the king — known as basileus — is confirmed by symbolic elements that surround him. The Homeric king overlay himself with sacred symbols as the celestial scepter given by Zeus. Further the king bears the title anax which is similar to the title of Zeus and this king has a personal divine protection. All this aspects delimitate the social position of basileus in this society connecting him with the supernatural world because of this the king became himself a different human being. The accumulation of geras (“advantage”) and time (“honour”), gained through heroic actions and given by Zeus, also help in the delimitation of basileus position. This allows us to reach a definition of homeric kingship strongly connected with the divinities.